Hey there! :)
1/2(n - 1) - 3 = 3 - (2n + 3)
Simplify.
1/2n - 1/2 - 3 = 3 - 2n - 3
Add like terms.
1/2n - 3 1/2 = -2n
Add 3 1/2 to both sides.
1/2n = -2n + 3 1/2
Then, add 2n to both sides.
1/2n + 2n = 3 1/2
Simplify!
2 1/2n = 3 1/2
Make everything into improper fractions!
5/2n = 7/2
Multiply everything by 2 to get rid of the denominators.
5/2n × 2 = 7/2 × 2
Simplify!
5n = 7
Divide both sides by 5.
n = 7/5
Hope this helped! :)
Answer:
[tex]\frac{7}{5} = n[/tex]
Step-by-step explanation:
[tex] \frac{1}{2} (n - 1) - 3 = 3 - (2n + 3) \\ [/tex]
Solve the brackets.
[tex] \frac{n}{2} - \frac{1}{2} - 3 = 3 - 2n - 3 \\ [/tex]
Make the denominator the same to solve the fractions.
[tex] \frac{n}{2} - \frac{1}{2} - \frac{3 \times 2}{1 \times 2} = 3 - 2n - 3 \\ [/tex]
Combine like terms.
[tex] \frac{n}{2} - \frac{1}{2} - \frac{6}{2} = - 2n \\ \\ \frac{n - 7}{2} = - 2n \: \: \: \: \: \: \: \: [/tex]
Use cross multiplication to solve for n.
[tex]n - 7 = - 4n \\ \\ - 7 = - 4n - n \\ \\ - 7 = - 5n \: \: \: \: \: \: \\ \\ \frac{ - 7}{ - 5} = \frac{ - 5n}{ - 5} \: \: \: \: \\ \\ \frac{7}{5} = n \: \: \: \: \: \: \: [/tex]
In which pair of triangles is Triangle EFG=Triangle RTS?
Answer:
The last picture or
The picture with 3 lines on EF and TR, 1 line one EG, 1 line on SR, 2 lines on ST and 2 lines on GF
Step-by-step explanation:
Since EF and RT have 3 lines and FG and TS have 2 lines, they are similar
Answer:
Last pair of triangles represent congruence.Step-by-step explanation:
If [tex]\triangle EFG \cong \triangle RTS[/tex], it can be deducted the following:
[tex]\angle E \cong \angle R\\\angle F \cong \angle T\\\angle G \cong \angle S[/tex]
Also,
[tex]EF \cong RT\\FG \cong TS\\EG \cong RS[/tex]
Notice that the last imag shows the correct congruence, because it shows the congruence between sides as we said before.
(9y+7)
Find the value of y and
the measures of all
angles.
(2y+98)°
Answer:
Both obtuse angles - 124°
Both acute angles - 56°
Step-by-step explanation:
The two given obtuse angles are equal. Therefore you get an equation
[tex]9y+7 = 2y+98\\7y=91\\y=13[/tex]
So the obtuse sizes of the two given angles are [tex]13*9+7=2*13+98=124[/tex]°
And the sizes of the acute angles are [tex]180-124=56[/tex]°
Without a clear relationship between the expression (9y+7) and the angle measurement (2y+98)°, we cannot find a unique value for y. However, the measure of the angle would vary with y according to the formula (2y+98)°.
Explanation:The given expression is (9y+7) and the measure of the angle is (2y+98)°. We aren't given a specific equation that links the expression to the measure of the angle, so we cannot find a unique value for y. However, if a particular relationship between the expression and the measure of the angle is provided, such as them being equal, we can use algebraic methods to solve for y.
As for measures of angles, in general, if we know the value of y, we can substitute that into the (2y+98)° to find the specific angle. Without knowing the value of y or a particular relationship between (9y+7) and (2y+98)°, we can say that the measure of the angle varies with y according to the formula (2y+98)°.
Learn more about Algebraic Representation here:https://brainly.com/question/21512696
#SPJ11
help pleaseeeee solve 3-x/2=>12
Answer:
x ≤-18
Step-by-step explanation:
3-x/2≥12
Subtract 3 from each side
3-3-x/2≥12-3
-x/2≥9
Multiply each side by -2 to clear the fraction. Remember to flip the inequality since we are multiplying by a negative
-3 * -x/2 ≤ -2 *9
x ≤-18
Answer:
x ≤ - 18
Step-by-step explanation:
Given
3 - [tex]\frac{x}{2}[/tex] ≥ 12
Multiply all terms by 2
6 - x ≥ 24 ( subtract 6 from both sides )
- x ≥ 18
Multiply both sides by - 1, remembering to reverse the sign as a consequence of multiply by a negative quantity.
x ≤ - 18
The table shows the approximate height of a projectile x seconds after being fired into the air.
Which equation models the height, y, x seconds after firing?
y = –10(x)(x – 5)
y = 10(x)(x – 5)
y = –10(x – 5)
y = 10(x – 5)
time in seconds height meters
x y
0 0
1 40
2 60
3 60
4 40
5 0
The equation y = -10 (x) (x - 5) models the height.
Option A is the correct answer.
What is an equation?An equation contains one or more terms with variables connected by an equal sign.
Example:
2x + 4y = 9 is an equation.
66x = 8 is an equation.
We have,
From the table,
We can make ordered pairs in the form of (x, y).
(0, 0), (1, 40), (2, 60), (3, 60), (4, 40), (5, 0).
So,
We will choose the equation that satisfies the ordered pairs.
y = -10 (x) (x – 5)
This can be used as the equation.
For (0, 0), (1, 40), (2, 60), (3, 60), (4, 40), (5, 0)
i.e x = 0, 1, 2, 3, 4, 5
y = -10 x 0 = 0
y = -10 x 1 x -4 = 40
y = -10 x 2 x -3 = 60
y = -10 x 3 x -2 = 60
y = -10 x 4 x -1 = 40
y = - 10 x 5 x 0 = 0
y = 10 (x) (x - 5)
This can not be used since the y value is a negative value.
y = -10 (x – 5)
This is not possible.
y = 10 (x – 5)
This is not possible.
Thus,
The equation y = -10 (x) (x - 5) satisfy the given table values.
Learn more about equations here:
https://brainly.com/question/17194269
#SPJ6
To find which equation models the height of a projectile \( y \) seconds after being fired based on the given data, we can substitute the given x-values (time in seconds) into each equation and check whether the result matches the corresponding y-values (height in meters).
Let's go through each of the given equations and the provided points one by one:
1. Equation \( y = -10(x)(x – 5) \)
When \( x = 0 \), the height \( y \) should be 0.
Substituting the value into the equation, \( y = -10(0)(0 – 5) = 0 \), which matches the given point (0, 0).
When \( x = 1 \), the height \( y \) should be 40.
Substituting the value into the equation, \( y = -10(1)(1 – 5) = -10(-4) = 40 \), which matches the given point (1, 40).
When \( x = 2 \), the height \( y \) should be 60.
Substituting the value into the equation, \( y = -10(2)(2 – 5) = -10(-1) = 60 \), which matches the given point (2, 60).
When \( x = 3 \), the height \( y \) should be 60.
Substituting the value into the equation, \( y = -10(3)(3 – 5) = -10(-2) = 60 \), which matches the given point (3, 60).
When \( x = 4 \), the height \( y \) should be 40.
Substituting the value into the equation, \( y = -10(4)(4 – 5) = -10(-1) = 40 \), which matches the given point (4, 40).
When \( x = 5 \), the height \( y \) should be 0.
Substituting the value into the equation, \( y = -10(5)(5 – 5) = -10(0) = 0 \), which matches the given point (5, 0).
Since all the points match perfectly with the results from Equation 1, we confirm that Equation 1 models the height of the projectile accurately. Therefore, the correct equation is:
\( y = -10(x)(x – 5) \)
This quadratic equation represents a parabolic trajectory, which is typical for the motion of a projectile under gravity, with no air resistance, and assuming that the projectile lands at the same level from which it was fired.
which equation represents a circle?
Answer:
C
Step-by-step explanation:
The equation of a circle centred at the origin is
x² + y² = r² ← r is the radius
Consider
[tex]\frac{x^2}{2^2}[/tex] + [tex]\frac{y^2}{2^2}[/tex] = 1, that is
[tex]\frac{x^2}{4}[/tex] + [tex]\frac{y^2}{4}[/tex] = 1
Multiply through by 4
x² + y² = 4 ← equation of circle
This is the equation of a circle centred at the origin with radius 2
What is the value of 2 over 3 to the power of 0 to the power of -3
Answer:
[tex]((\frac{2}{3})^0)^{-3}=1[/tex]
Step-by-step explanation:
We need to find the value of [tex]((\frac{2}{3})^0)^{-3}[/tex]
Solving:
We know, [tex](a^b)^n = a^{b*n}[/tex]
[tex]((\frac{2}{3})^{0*-3})[/tex]
[tex](\frac{2}{3})^0[/tex]
a^0 = 1
so,
[tex](\frac{2}{3})^0=1[/tex]
So, the value of [tex]((\frac{2}{3})^0)^{-3}=1[/tex]
coordinates of the vertex
Answer:
(0, 3)Step-by-step explanation:
The vetex form of an equation of a parabola y = ax² + bx + c:
y = a(x - h)² + k
(h, k) - coordinates of a vertex
We have the equation y = 3x² + 3.
y = 3(x - 0)² + 3 → h = 0, k = 3
Mr. Wilson wrote the function fx) = 7x - 15 on the chalkboard. What is the value of this function for f(6)?
A 27
B 37
C 42
D 57
Answer: 27
Step-by-step explanation:
F(6)=42-15=27
Answer:
A 27
Step-by-step explanation:
f(x) = 7x - 15
Let x=6
f(6) = 7*6 -15
= 42 -15
= 27
A set of equations is given below: equation C:y=5x+10 equation D:y=5x+2 which of the following best describes the solution to the given set of equations? One solution no solution two solutions infinitely many solutions
Answer:
The system has no solution
Step-by-step explanation:
we have
y=5x+10 -----> equation C
The slope of the equation C is m=5 and the y-intercept is b=10
y=5x+2 -----> equation D
The slope of the equation C is m=5 and the y-intercept is b=2
Remember that
If two lines are parallel, then their slopes are the same
Equation C and equation D are parallel lines with different y-intercept
therefore
The system has no solution (the lines do not intersect)
-3(6f - 12) = 36 - 18f
Answer:
Step-by-step explanation:
The given expression is:
-3(6f - 12) = 36 - 18f
To prove that L.H.S=R.H.S:
Multiply -3 (6f-12)
-3(6f)-3(-12)
=-18f+36
=36-18f
Hence it is proved that L.H.S = R.H.S....
For what values of m dose the graph of y=3x^2+7x+m have two x-intercepts?
Answer:
[tex]\large\boxed{m<\dfrac{49}{12}}[/tex]
Step-by-step explanation:
x-intercepts are for y = 0.
Put y = 0 to the equation y = 3x² + 7x + m.
3x² + 7x + m = 0Calculate the discriminant of quadratic equation ax² + bx + c = 0:
Δ = b² - 4ac
if Δ < 0, then an equation has no solution
if Δ = 0, then an equation has one solution
if Δ > 0, then an equation has two solution.
3x² + 7x + m = 0a = 3, b = 7, c = m
Δ = 7² - 4(3)(m) = 49 - 12m
Two x-intercepts for Δ > 0.
Solve the inequality:
[tex]49-12m>0[/tex] subtract 49 from both sides
[tex]-12m>-49[/tex] change the signs
[tex]12m<49[/tex] divide both sides by 12
[tex]m<\dfrac{49}{12}[/tex]
The values of m that make the graph of y=3x²+7x+m have two x-intercepts are m less than 49/12.
Explanation:To find the values of m that make the graph of the equation y = 3x² + 7x + m have two x-intercepts, we need to determine when the discriminant is greater than zero. The discriminant can be calculated using the formula b² - 4ac, where a is the coefficient of x², b is the coefficient of x, and c is the constant term. In this case, a = 3, b = 7, and c = m. Setting the discriminant greater than zero and solving for m, we get:
7² - 4(3)(m) > 0
Simplifying the equation, we have:
49 - 12m > 0
Now, we can solve for m by isolating it on one side of the inequality:
-12m > -49
m < 49/12
Therefore, for any value of m that is less than 49/12, the graph of y = 3x² + 7x + m will have two x-intercepts.
Learn more about Quadratic Equations here:
https://brainly.com/question/30098550
#SPJ2
Joe has one book each for algebra, geometry, history, psychology, Spanish, English and Physics in his locker. How many different sets of three books could he choose?
Answer:
There are 35 different sets of 3 books Joe could choose
Step-by-step explanation:
* Lets explain how to solve the problem
- Combination is a collection of the objects where the order doesn't
matter
- The formula for the number of possible combinations of r objects from
a set of n objects is nCr = n!/r!(n-r)!
- n! = n(n - 1)(n - 2)................. × 1
Lets solve the problem
- Joe has one book each for algebra, geometry, history, psychology,
Spanish, English and Physics in his locker
∴ He has seven books in the locker
- He wants to chose three of them
∵ The order is not important when he chose the books
∴ We will use the combination nCr to find how many different sets
of three books he can choose
- The total number of books is 7
∴ n = 7
∵ He chooses 3 of them
∴ r = 3
∵ 7C3 = 7!/3!(7 - 3)! = 7!/3!(4!)
∴ [tex]7C3=\frac{(7)(6)(5)(4)(3)(2)(1)}{[(3)(2)(1)][(4)(3)(2)(1)]}=35[/tex]
∴ 7C3 = 35
* There are 35 different sets of 3 books Joe could choose
The data shown on the scatter plot below demonstrates the relationship between the time of day and the total number
of calories that a teenager consumes throughout the day.
That as time ___________,
the total number of calories that a teenager consumes throughout the day
___________.
Blank A options:
Stays the same
Increases
Decreases
Blank B options:
Stays the same
Decreases
Increases
Answer:
Good question! The correct answer is a) increases and b) increases.
While the pair of answers a) decreases and b) decreases or the pair a) stays the same and b) stays the same would be technically correct answers, this is the best way of describing the trend of the scatter plot; typically, trends are described by how the dependent or y-variable responds to the independent or x-variable increasing.
Answer:
a) increases and b) increases.
Step-by-step explanation:
18-r=12
[tex]18 - r = 12[/tex]
Answer:
r = 6Step-by-step explanation:
18 - r = 12 subtract 18 from both sides
18 - 18 - r = 12 - 18
-r = -6 change the signs
r = 6
Check
18 - 6 = 12 CORRECT
Leila bought 3 bananas, which weighed a total of 3/4 of a pound . if each banana weighed the same amount , what is the weight of each banana ?
Answer:
I think the answer is A
Step-by-step explanation:
Answer:
C.
Step-by-step explanation: The other answer was not right on edge* but i belive that it is C.
I need some help guys
Answer:
Q1: D
Q2: D
Step-by-step explanation:
Question No 1:
The given sequence is:
-2, 0, 3, 7, ...
We can easily determine that this is not an arithmetic sequence because the common difference between terms is not same.
i.e.
0-(-2) = 0+2 = 2
3-0 = 3
7-3 = 4
As the common difference is not same so the sequqnce is not an arithmetic sequence.
Question no 2:
Given sequence is:
28, 18, 8, -2, ..
We can see that the common difference is -10 i.e 18-28 = -10
And it is same for all numbers.
The standard formula for arithmetic sequence is:
[tex]a_n=a+(n-1)d\\Here\\a = 28\\d=-10\\So,\\a_n=28+(-10)(n-1)\\a_n=28-10n+10\\a_n=38-10n[/tex]
Now for the 52nd term:
[tex]a_{52} = 38-10(52)\\= 38-520\\=-482[/tex] ..
The sum of a number and 20 is no more than the sum of the square of the number and 9.
Which of the following inequalities can be used to determine this unknown number?
A. x + 20 < (X + 9)2
B.
X+ 20 x2 + 9
C.
X+ 20 = (x + 9)2
D.
X + 20 < x2 +94
A is the correct answer.
break down the word problem.
You also have to recognize key words which figure into mathematical symbols.
ex. sum of a number and 20 is x+20
square of the number and 9 is (x+9)^2
please vote my answer brainliest! thanks.
The given line passes through the points (0, -3) and (2, 3).
What is the equation, in point-slope form of the line that is
parallel to the given line and passes through the point
-1, - 1)?
y+1=3(x+1)
y+1=-=(x + 1)
-
532
v+1={(x+1)
y+1 =3(x+1)
Mark this and return
Save and Exit
S
Answer:
[tex]y+1=3(x+1)[/tex]
Step-by-step explanation:
Ok so we are looking for line parallel to the line containing points (0,-3) and (2,3).
Parallel lines have the same slope.
So let's find the slope of the line containing the points (0,-3) and (2,3).
You can use the formula [tex]m=\frac{y_2-y_1}{x_2-x_1}[/tex].
However, I just like to line up the points vertically and subtract them vertically, then put 2nd difference over 1st difference. Like this:
(0 , -3)
-(2 , 3)
-----------
-2 -6
So the slope is -6/-2 or just 3.
So the slope of the line we are looking for has slope 3 (or m=3) and your line should contain the point (-1,-1).
The point slope form of a line is:
[tex]y-y_1=m(x-x_1)[/tex] where [tex]m[/tex] is the slope and [tex](x_1,y_1)[/tex] is a point you know on the line.
So we just plug into that equation now. That gives us:
[tex]y-(-1)=3(x-(-1))[/tex]
Simplify a bit:
[tex]y+1=3(x+1)[/tex]
Answer:
The answer is: y+1=(3x+1)
Step-by-step explanation:
A cube has side length 0.7 metres.
Work out the total surface area of the cube.
Give your answer in square centimetres
Answer:
2.94cm^2
Step-by-step explanation:
If you're referring to the mathswatch question, this gets you 2/3 :)
Write the standard form of the equation of a line if the point on the line nearest to the origin is at (6, 8).
Answer:
[tex]\large\boxed{y=\dfrac{4}{3}x}[/tex]
Step-by-step explanation:
The line passes through the origin has an equation y = mx
m - slope
The formula of a slope of a line passes through the origin
and a point (x, y):
[tex]m=\dfrac{y}{x}[/tex]
We have the point (6, 8). Substitute:
[tex]m=\dfrac{8}{6}=\dfrac{8:2}{6:2}=\dfrac{4}{3}[/tex]
Finally:
[tex]y=\dfrac{4}{3}x[/tex]
Given that the first term and the common difference of an arithmetic progression are 6 and 3 respectively. Calculate the sum of all terms from 4th term to the 14th term.
Answer:
330
Step-by-step explanation:
Evaluate the sum of 14 terms and subtract the sum of the first 3 terms
The sum to n terms of an arithmetic sequence is
[tex]S_{n}[/tex] = [tex]\frac{n}{2}[/tex] [ 2a₁ + (n - 1)d ], so
[tex]S_{14}[/tex] = 7 [ (2 × 6) + (13 × 3)]
= 7(12 + 39) = 7 × 51 = 357
[tex]S_{3}[/tex] = 6 + 9 + 12 = 27
Sum of terms from 4 th to 14 th = 357 - 27 = 330
Please Help.
Tracey built a small boat and recorded the distance it traveled. The table below shows the distance traveled (f) during the first 4 seconds after starting (p).
Elapsed Time
(seconds) Distance Traveled
(feet)
1 4.2
2 8.4
3 12.6
4 16.8
Which of the following equations represents the relationship between the distance traveled and the elapsed time?
p = 4.2f
f = 4.2p
p = 4.2 + f
f = 4.2 + p
Answer:
Expressing the distance from the shore by the time needed to reach that distance at an invariable speed of 4.2f/s then f=4.2 p
Answer:
f=4.2p
Step-by-step explanation:
Determine the theoretical probability of rolling a number larger than two and a standard 66 sided cube
Answer:
Required probability = 2/3
Step-by-step explanation:
When rolling a 6 sided die, the out comes are
1, 2, 3, 4, 5 and 6
Total number of outcomes = 6
To find the probability
The required outcome is a number greater than 2, therefore possible outcomes are,
3, 4, 5, and 6
Number of possible outcomes = 4
Required probability = 4/6 = 2/3
Answer:
Determine the theoretical probability of rolling a number larger than 2 on a standard 6-sided cube.
2/3
Step-by-step explanation:
What is the following quotient? sqrt 6 + sqrt 11 / sqrt 5 +sqrt 3
The answer is B) Link below
Answer:
B
Step-by-step explanation:
I just did it
what is the simplest form of 3√27a3b7
Answer:
[tex]3ab^2\sqrt[3]{b}[/tex]
if the problem was [tex]\sqrt[3]{27a^3b^7}[/tex].
Step-by-step explanation:
Correct me if I'm wrong by I think you are writing [tex]\sqrt[3]{27a^3b^7}[/tex].
[tex]\sqrt[3]{27a^3b^7}[/tex]
I'm first going to look at this as 3 separate problems and then put it altogether in the end.
Problem 1: [tex]\sqrt[3]{27}=(3)[/tex] since [tex](3)^3=27[/tex].
Problem 2:[tex]\sqrt[3]{a^3}=(a)[/tex] since [tex](a)^3=a^3[/tex]
Problem 3: [tex]\sqrt[3]{b^7}[/tex]. This problem is a little harder because [tex]b^7[/tex]is not a perfect cubes like the others were. But [tex]b^7[/tex] does contain a factor that is a perfect cube. That perfect cube is [tex]b^6[/tex] so rewrite [tex]b^7[/tex] as [tex]b^6 \cdot b^1[/tex] or [tex]b^6 \cdot b[/tex].
So problem 3 becomes [tex]\sqrt[3]{b^6 \cdot b}=\sqrt[3]{b^6}\cdot \sqrt[3]{b}=b^2 \cdot \sqrt[3]{b}[/tex]. The [tex]b^2[/tex] came from this [tex](b^2)^3=b^6[/tex].
Anyways let's put it altogether:
[tex]3ab^2\sqrt[3]{b}[/tex]
Graph the numbers 3, -5/2, 0, 3/4 on a number line
Answer:
Step-by-step explanation:
If it's any help, these numbers, rearranged in ascending order, are
-5/2, 0, 3/4, 3.
Place a bold dot at -5/2 on your number line. This is halfway between -2 and -3. Next, place such a dot at 0. Next, place a dot at 3/4, which is between 0 and 1 but closer to 1. Last, place a dot at 3.
Which represents the solution set to the inequality 5.1(3 + 2.2x) > –14.25 – 6(1.7x + 4)
Answer:
x > -52.5.
Step-by-step explanation:
5.1(3 + 2.2x) > –14.25 – 6(1.7x + 4)
15.3 + 11.22x > -14.25 - 10.2x - 24
1.02x > -14.25 - 24 - 15.3
1.02x > -53.55
x > -53.55 / 1.02
x > -52.5.
Answer:
(–2.5, ∞)
Step-by-step explanation:
Question 2 of 10
2 Points
If you vertically stretch the quadratic parent function, Fx) = x2, by multiplying
by 7, what is the equation of the new function?
O A. G(x) = x2 - 7"
O B. G(x) = (x + 7)2
O C. G(x) = (7x)2
O D. G(x) = 7x2
SUBMIT
Answer:
D. G(x) = 7x2
Step-by-step explanation:
Given a function f(x), the function kf(x) is stretched by a factor of k. In this case, if we stretch the function f(x) = x^2 by a factor of 7, the new function is going to be:
g(x) = 7x^2. Therefore, the correct option is option D.
Mixed 3 liters 20% solutions with 2 liters 70% solution. What’s the final concentration,
Answer:
(3×20%+2×70%)/3+2=40%
Step-by-step explanation:
Assuming the potions are the same type or do mix then probably the concentration of the potion depends on the type of reaction they have to each other.
Yet we can average the percentage of the active ingredient by the principle mentioned above
Answer:
The final concentration is 40%.
Step-by-step explanation:
Let x the concentration of final solution.
3 liters of solution (1) with 20% concentration is mixed with 2 liters of 70% solution producing (3 + 2) = 5 liters of x% mixture.
Now 3 × (20%) + 2 × (70% = 5 (x%)
3 × 0.2 + 2 × 0.7 = 5 (0.1x)
0.6 + 1.4 = 0.05x
2 = 0.5x
x = 2/0.05
= 40%
The final concentration is 40%.
Solve the equation for x by graphing. -4x-1=5^x+4
Answer:
x=-1.282
Step-by-step explanation:
To solve the equation [tex]-4x-1=5^x+4[/tex] by graphing, you have to plot graphs of two functions:
[tex]y=-4x-1\\ \\y=5^x+4[/tex]
The x-coordinate of the point of intersection is the solution of the equation.
The graph of the function [tex]y=-4x-1[/tex] is shown in attached diagram with red line and the graph of the function [tex]y=5^x+4[/tex] is shown with blue curve.
The point of intersection has approximate coordinates (-1.282, 4.127), so the solution (correct to three decimal places) of the equation is x=-1.282